Toxic plants from the perspective of a "Quilombola" community in the Cerrado region of Brazil. (1st March 2023) - de Castro Santos Paim, Ricardo; Ferreira de Paula, Luiza Gabriella; Soares, Débora Moreira; Gonçalves Rocha, Tarik Fernandes; Ribeiro, Amanda Lopes; Barros, Natália; Carrião dos Santos, Fabrício; Ferreira, Heleno Dias; Gomes-Klein, Vera Lúcia; Soto-Blanco, Benito; Paes de Oliveira-Filho, José; Jorge da Cunha, Paulo Henrique; et al.
Abstract: A multi-disciplinary team surveyed ranchers at the Kalunga Historical and Cultural Heritage Site, in the Cerrado region of west central Brazil, to determine impacts promoted by toxic plants on cattle. The expedition to the Kalunga region was carried out by Brazilian and American researchers. Previously selected cattle ranch properties from "Vão das Almas", "Engenho II" and "Vão do Moleque" were visited. Twenty-four interviews were carried out with cattle ranchers and a questionnaire was applied to obtain information about outbreaks of native plant poisoning and their effects on livestock, and the use of local plants in phytotherapy. We classified problematic plants into three distinct categories. First, the toxic plants most cited by residents causing cattle losses were the flowers of Caryocar brasiliense Cambess ("pequi"), the fruits of Terminalia corrugata (Ducke) Gere & Boatwr. ( Buchenavia tomentosa Eichler - "mirindiba" or "pau-pilão"), Eugenia dysenterica (Mart.) DC ("cagaita"), and Palicourea marcgravii A. St. Hil ("erva-café" or "cafezinho"). Secondly, other plants considered toxic, but causing less severe losses were Emmotum nitens (Benth.) Miers ("casco d'anta"), Indigofera lespedezioides (Kunth) ("timbozinho"), Ricinus communis L. ("mamona"), Pteridium esculentum (G. Forst.) Cockayne ("samambaia"), Stryphnodendron adstringens (Mart.) Coville ("barbatimão"), and Actinocladum verticillatum (Nees) McClure ex Soderstr. ("cambaúba"). The most important finding was the identification of the C. brasiliense flower as potentially toxic to cattle, which must be subject for future research. Further, we confirmed the toxicity and importance of P. marcgravii, E. dysenterica, and Terminalia corrugata . The survey highlighted phytotherapy plants used by the community, and greatly increased awareness by local livestock producers of poisonous plants for management purposes. We conclude that ethnobotanical knowledge, especially from the traditional community, is essential to understand livestock losses to toxic plants, and should be valued not only for reducing livestock losses, but also for cultural importance to the Kalunga communities in the Cerrado. Graphical abstract: Image 1 Highlights: Ethnobotanical knowledge impacts plant surveys. Ethnobotanical knowledge is important for its impact on culture and Cerrado cattle production. Speech analysis is an innovative and useful methodology for toxicology surveys. Flowers of Caryocar brasiliense are potentially toxic to cattle. Palicourea marcgravii, Eugenia dysenterica, Terminalia corrugata are toxic for cattle.